Location of ischemia and ischemic pain intensity affect spatiotemporal parameters and leg muscles activity during walking in patients with intermittent claudication - Céline Guilleron (Nature Portfolio, 2021)
Abstract The ways in which locations of ischemia and ischemic pain affect spatiotemporal gait parameters and leg electromyographic activity during walking have never been investigated in patients with peripheral arterial disease presenting intermittent claudication. Two groups were classified according to unilateral location of ischemia (distal, n = 10, or proximo-distal, n = 12). Patients described pain and three gait phases—initial pain-free, onset of pain and maximum pain—were analyzed. Patients with proximo-distal ischemia walked less (230 ± 111 m vs 384 ± 220 m), with increased step length, step time (+ 5.4% and + 5.8%) and reduced cadence (− 8.2%), than patients with distal ischemia. In both, the peaks of vertical ground reaction force were reduced in maximum pain (Peak1-distal: − 11.4%, Peak1-proximo-distal: − 10.3%; Peak2-distal: − 11.8%, Peak2-proximo-distal: − 9.0%). In the proximo-distal group, tibialis anterior activation peak and time were lower than in the distal group (− 4.5% and − 19.7%). During the maximum pain phase, this peak decreased only in the proximo-distal group (− 13.0%), and gastrocnemius medialis activation peak and time decreased in both groups (− 2.5% in distal and − 4.5% in proximo-distal). Thus, proximo-distal ischemia leads to more adverse consequences in gait than distal ischemia only. Increasing ischemic pain until maximum, but not onset of pain, induced gait adaptations.